The Effect of Concurrent Endurance and Resistance Exercise on Plasma Levels of Vascular Endothelial Growth Factor and Endostatin in Inactive Women - Saeedeh Shadmehri; Mozhgan Ahmadi (Islamic Azad University, 2016)
Introduction: The present study aims to investigate the effect of one concurrent endurance and resistance exercise training session on plasma levels of vascular endothelial growth factor (VEGF) and endostatin in inactive women. Methods: In this quasi-experimental study, 12 inactive female university students were divided into control (average age=20.0 ±1.78 years, height = 161.3 ±50 cm, weight = 58.83±5.71 kg, BMI = 22.38±3.23 kg/m2) and exercise (average age =19.5±1.04 years, height = 163.1±3.79 cm, weight = 58.67±7.69 kg, BMI =22.35±2.22 kg/m2) groups. The endurance exercise was performed on a treadmill with 65% of MHR for 16 minutes. The resistance exercises of four movements including leg press, chest compression, armpit and leg stretch were performed at 50% 1RM in two sets with 10 repetitions and 1-2 minutes' rest intervals between sets. Data were analyzed using dependent t-test and independent t-test to determine differences within the group and between-group at pthe control group (p= 0.168). Conclusion: According to the findings, it seems that one session of concurrent endurance and resistance exercise has a positive influence on VEGF and probably it can help to improve the condition of angiogenesis.